Elaboración e implementación de estrategias para la prevención de incendios forestales y el protocolo de conservación de la biodiversidad en el Bosque Protector La Prosperina - ESPOL - Sánchez Aguas, David Francisco (2025)
Forest fires have become a growing global environmental issue, exacerbated by climate change. Their frequency and intensity increase, especially during dry periods, when environmental conditions lower the ignition point of vegetation, making it more susceptible to combustion. These fires negatively impact ecosystems, biodiversity, and nearby communities. Effective fire management and preventive strategies are essential to mitigate their effects and protect natural resources.